Analisis Break Even Point Perencanaan Laba pada Mochi Kaswari Bakat Jaya - Siti Hana; Gatot Wahyu Nugroho (AKUNTANSI 45, 2024)
The business world in Indonesia is very competitive. It is no surprise that so many businesses are thriving, progressing, and succeeding. However, some have fallen so far behind that they have to declare bankruptcy. Therefore, companies need to plan their profits as well as possible in order to avoid bankruptcy. One thing that management can do to face the challenges of corporate competition is to be able to organize its operations effectively. The qualitative method is a method with a research process based on understanding a phenomenon with the approach that the data produces descriptive analysis in the form of oral sentences from the object of research. This research uses a qualitative analysis approach and is descriptive, with data collection methods using observation, interviews, documentation, and quantitative analysis techniques. From the results of the Break Even Point calculations that have been carried out, it will reach the break-even point in sales if in 2021 it must be able to sell production equal to Rp. 183,259,260 or more than that nominal, in 2022 it must be able to sell production equal to Rp. 185,775,000 or more than that nominal, the year must be able to sell production equal to Rp. 283,779,999